Oil tour Mexico '97: photographs on the (Greenpeace actions against) the pollution by the oil industry of the coastal areas in eastern Mexico (with captions) (1997)
Oil tour Mexico '97: photographs on the (Greenpeace actions against) the pollution by the oil industry of the coastal areas in eastern Mexico (with captions).